Effect Acupuncture for Low Back Pain; Biochemical and Protein Profile Analysis - Wardoyo, Suwaji Handaru; Badri, Solichan (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Low back pain (LBP) is one of the common symptoms experienced by some of the world community. Acupuncture as a method of healing a disease offers a solution for LBP symptom. This study aimed to determine the effect of acupuncture with local and Yamamoto New Scalp Acupuncture (YNSA) points with biochemical analysis related to total protein, albumin, and globulin, and analysis of blood serum protein profiles using the SDS-PAGE method. This research was conducted using sterile acupuncture needles that inserted in patients with several local points, namely BL22 (Sanjiaoshu), BL23 (Shenshu), BL24 (Qihaishu), BL25C (Dachangshu), and BL26C (Guanyuanshu) and combined with the YNSA points through somatotope D points and extra lumbar points H and I. Blood serum was collected for total protein, albumin, and globulin analysis. That blood serum was also used for protein profile analysis using Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) method. The results showed that six times of acupuncture treatments gave positive correlation in total protein, albumin, and globulin. Analysis of blood serum protein profiles using SDS-PAGE showed a protein band of about 12 KDa and it might be a interleukin-13 protein. The results were expected can be useful as scientific information especially related to acupuncture for LBP treatment and this of about 12 KDa protein band can be used as biomarker candidates for the symptoms.